Implementasi Pembelajaran IPS pada Masa Pandemi Covid-19 - Nurpratiwiningsih, Laelia (UNIB Press, 2021)
The Covid 19 pandemic is a big problem for people's lives in the world. The purpose of this study is to find out ips learning in the covid 19 period. One of the highlights in the world of education, where learning activities are carried out online. This learning activity automatically involves teachers and students, as well as parents because learning is done at home. Implementation of learning in rural areas with facilities. This also happened in SD Negeri Ciawi District Banjarharjo Brebes Regency. The method used is a qualitative descriptive survey. Instruments used in the form of interviews are given to learners, teachers and primary school principals. Observations can be used as support in data retrieval. The focus of this study is on learning IPS covid 19. Data analysis techniques use source triangulation. Analyze data by subtracting, viewing and verifying data. The results showed that the covid-19 pandemic had an impact and there were constraints on learning for learners, teachers, and principals. Where learning is done online and offline. With this pandemic all remain vigilant and keep themselves in accordance with health protocols recommended by the government to avoid the coronavirus.